Megengan Ritual: Tracing Existential Meaning in Javanese Culture through Philosophy of Anthropology - Ahmad Mustakim (Javano Islamicus, 2025)
Megengan is not just a ritual, but a process of internalization of deep religious and moral values, which is reflected in the daily attitudes and actions of Javanese people during Ramadan. This tradition begins with various preparations such as cleaning themselves, houses, and the surrounding environment, symbolizing the cleansing of the body and soul in order to welcome the holy month with a pure heart and a calm heart. They may also prepare and distribute special food called apem, which symbolizes apology and forgiveness, in accordance with the Javanese philosophy of harmony. This ritual combines religious elements and traditional Javanese values, strengthening social bonds and a sense of community, as well as self-reflection to fi nd a balance between secular and spiritual needs. Values such as unity, harmony and self-control are deeply embedded in this tradition and we can see how the younger generation is taught to value and preserve cultural heritage. This study analyzes the existential meaning of the Megengan ritual through an anthropological-philosophical approach, reveals the philosophical and spiritual values in the practice of Megengan, and examines the role of Megengan in the formation of cultural identity of the role played by Javanese society. The research findings reveal the deep existential meaning of Megengang, how this ritual helps individuals find the meaning of life and self-identity, and serves as a means to preserve and strengthen the Javanese cultural identity that is expected to be displayed.